Unmanned aerial systems-aided post-flood peak discharge estimationin ephemeral streams - Andreadakis, Εmm.; Diakakis, Μ.; Vassilakis, Emm.; Antoniadis, A.; Andriopoulos, P.; Spyrou, Ν.; Nikolopoulos, E. (Remote Sensing, 2020)
The spatial and temporal scale of flash flood occurrence provides limited opportunities for observations and measurements using conventional monitoring networks, turning the focus to event-based, post-disaster studies. Post-flood surveys exploit field evidence to make indirect discharge estimations, aiming to improve our understanding of hydrological response dynamics under extreme meteorological forcing. However, discharge estimations are associated with demanding fieldwork aiming to record in small timeframes delicate data and data prone-to-be-lost and achieve the desired accuracy in measurements to minimize various uncertainties of the process. In this work, we explore the potential of unmanned aerial systems (UAS) technology, in combination with the Structure for Motion (SfM) and optical granulometry techniques in peak discharge estimations. We compare the results of the UAS-aided discharge estimations to estimates derived from differential Global Navigation Satellite System (d-GNSS) surveys and hydrologic modelling. The application in the catchment of Soures torrent in Greece, after a catastrophic flood shows that the UAS-aided approach succeeded in determining peak discharge with high accuracy. The technique proved to be particularly effective, providing flexibility in terms of resources and timing, although there are certain limitations to its applicability. The application highlighted important advantages and certain weaknesses of these emerging tools in indirect discharge estimations, which we discuss in detail.